ANALISA PENGARUH INITIAL TRUST TERHADAP ACTUAL USAGE MELALUI BEHAVIORAL INTENTION DALAM APLIKASI DIGITAL PAYMENT OVO - Jocellynne Saintz (Jurnal Strategi Pemasaran, 2019)
The purpose of this research aims to analyze the influence of Initial Trust towards Acual Usage through Behavioral Intention in OVO digital payment application. This research was conducted by distributing questionnaires to 100 respondents who had used OVO digital payment application at least twice in the last three months and had done top-up. This research use the Initial Trust (X1) variable with the indicators Affect-based Trust, Cognition-based Trust, dan Institution-based Trust, Actual Usage variable (Y1) with the indicators Conscientiousness, Extraversion, Agreeableness, Openness, Behavioral Intention variable (Z1) with the indicators Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Condition. The results show: (1) Initial Trust influence significantly to Behavioral Intention; (2) Behavioral Intention influence significantly to Actual Usage; (3) Initial Trust influence significantly to Actual Usage